2013
DOI: 10.3109/21614083.2013.772056
|View full text |Cite
|
Sign up to set email alerts
|

Beyond accreditation systems – the identification of different implementation models for CME across Europe

Abstract: We have previously published the results of a comprehensive research project which was conducted in 11 European countries in 2010/2011 to establish a detailed database on the implementation of CME in these countries, including underlying structures, roles and responsibilities, and funding models. Special attention was given to the role of the various stakeholders such as Ministry of Health/government, physician associations/societies/chambers, and universities in addition to the positioning of CME within the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…As shown in the review, a number of challenges exist in LLMICs that render the CPD system development and implementation much more complex, namely limited financing, technological barriers, a lack of human resources and structures to maintain a CPD system, negative attitudes, and a dearth of CPD materials and activities that are relevant to the context and available in the local language. As highlighted by others, and also in this review, government level engagement can ensure resources, including financing, are mobilized, and can provide support for setting standards; they may also pay a role in enforcement [ 1 , 10 , 13 , 17 ]. Vakani et al (2022) observed, however, that government involvement and effectiveness are often related to political stability within a country, and thus the larger context must be considered as well [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the review, a number of challenges exist in LLMICs that render the CPD system development and implementation much more complex, namely limited financing, technological barriers, a lack of human resources and structures to maintain a CPD system, negative attitudes, and a dearth of CPD materials and activities that are relevant to the context and available in the local language. As highlighted by others, and also in this review, government level engagement can ensure resources, including financing, are mobilized, and can provide support for setting standards; they may also pay a role in enforcement [ 1 , 10 , 13 , 17 ]. Vakani et al (2022) observed, however, that government involvement and effectiveness are often related to political stability within a country, and thus the larger context must be considered as well [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Насамперед слід зауважити, що прийняття рі-шень при обґрунтуванні стратегії контролю знань у системі післядипломної медичної освіти здійсню-ється в умовах як певної невизначеності щодо рівня знань слухачів, їх сприйняття навчального матері-алу, так й відсутності єдиних критеріїв успішнос-ті процесу [9]. Тому вважаємо, що контроль знань може бути валідним, якщо забезпечується режим постійного моніторингу.…”
Section: результатиunclassified
“…There are international reviews regarding CME practices and requirements in European countries. 12,18–20 However, there are no recent reviews on the CME status in the SEAR and Eastern Mediterranean Region (EMR) to monitor progress in implementing formal CME in these regions. This research investigates “What is the status of CME provision and its regulation for health care professionals in SEAR and EMR?” These are two of the six regions defined by the WHO: Africa, America, Europe, Western Pacific, EMR, and SEAR.…”
mentioning
confidence: 99%